THE IMPACT OF REALISTIC MATHEMATICS EDUCATION (RME) APPROACH ASSISTED BY UNIT CUBE MODELS ON FIFTH GRADE STUDENTS' UNDERSTANDING OF CONCEPTS IN MIN 26 ACEH BESAR - Novi Selvia; Silvia Sandi Wisuda Lubis; Zikra Hayati; Zulkipli Lessy (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This research is motivated by the low understanding of mathematical concepts at MIN 26 Aceh Besar. Data obtained from 26 students show that 27.88% of students can solve problems with the indicator of restating a concept, 41.35% can solve problems with the indicator of identifying examples and non-examples of a concept, and 30.77% can solve problems with the indicator of identifying objects according to specific properties in line with the concept. The low understanding of these concepts is due to the lack of students' desire to learn the material presented and their failure to pay attention to the material explained by the teacher. This study aims to determine the impact of the Realistic Mathematics Education (RME) approach assisted by unit cube props on the conceptual understanding of fifth-grade students at MIN 26 Aceh Besar. This research uses a quantitative method with a true-experimental design. The population in this study comprises all fifth-grade students at MIN 26 Aceh Besar, while the samples are class Va, consisting of 26 students, and class Vb, consisting of 23 students. The instrument used in this research is a test to measure students' conceptual understanding. The data collection technique is a test in the form of a pre-test and post-test. Data analysis techniques include converting ordinal data into interval data using the Method of Successive Intervals (MSI), creating frequency distribution lists, calculating average values, conducting normality tests, homogeneity tests, equality of two means tests, regression tests, and hypothesis tests. Based on the analysis results, the average score obtained in the experimental class pre-test is 12.59 and in the control class is 11.17. Meanwhile, the post-test average score for the experimental class is 18.598, and for the control class, it is 13.672. The analysis results show that t_calculated = 9.425 and t_table = 1.677; since t_calculated > t_table, Ho is rejected, and Ha is accepted.Keywords: Realistic Mathematics Education, Unit Cube Props